Atypical goblet cell hyperplasia in congenital cystic adenomatoid malformation as a possible preneoplasia for pulmonary adenocarcinoma in childhood: a genetic analysis - Stacher, Elvira (2004)
Congenital cystic adenomatoid malformation (CCAM) of the lung is a congenital lesion that is sometimes complicated by bronchioloalveolar adenocarcinoma (BAC). In some cases foci of atypical goblet cell hyperplasia (AGCH) can be found within the cysts. It has been proposed that CCAM and AGCH predispose to the development of BAC. The present study used comparative genomic hybridization (CGH) to screen 22 cases of CCAM (epithelium, surrounding normal lung tissue, and both preneoplastic and neoplastic lesions) for chromosomal imbalances. Of these 22 cases, 10 were CCAM type 1, 10 were type 2, and 2 were type 3. Of the 10 cases of CCAM type 1, 2 were associated with AGCH, 1 was associated with atypical adenomatous hyperplasia (AAH) and associated tubular adenocarcinoma (AC), and 2 were associated with BAC (1 mucinous and 1 predominantly nonmucinous). The present study also involved immunohistochemistry for interleukin (IL)-13, IL-4 receptor-[alpha] (IL-4r[alpha]), cytokines involved in the differentiation of goblet cells, and mucin 2 protein (Muc2). Chromosomal aberrations were not detected in the epithelium or the surrounding normal lung tissue, whereas varying aberrations were found in the neoplastic lesions. The most frequent genomic imbalances observed in both AGCH and the carcinomas were gains in chromosomes 2 and 4. Interestingly, a predominance of gains was also reported in AC of nonsmokers. Chromosomal aberrations in AGCHs arising in CCAMs support their preneoplastic status. Nuclear expression of IL-13, IL-4r[alpha], and Muc2 was detected in AGCH, whereas a cytoplasmic and nuclear reaction was seen in normal epithelium. This likely reflects an association with goblet cell differentiation, but it also drives proliferation in AGCH.